Mass Culture of Arthrospira Platensis Utilizing Aerobically Digested Palm Oil Mill Effluent (Adpome) - Aguol, Kennedy Aaron (2003)
A series of experiments were conducted to develop a mass culture technique of Arthrospira platensis, a blue-green alga, in freshwater and brackishwater (1S ppt) using different concentrations (1, 2, 3, 4 and S%) of aerobically digested palm oil mill effluent (ADPOME) in two trials. The cell growth, chlorophyll a, total protein, carbohydrate, lipid contents and fatty acid profile were also studied. Physiochemical water quality parameters (temperature, dissolved oxygen, pH, salinity, surface irradiance, underwater irradiance, optical density, total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, total nitrogen, phosphate phosphorus, total phosphorus, chemical oxygen demand, biochemical oxygen demand and total dissolved organic carbon) were also measured throughout the study. Algal cell growth was best in 4% ADPOME, both in the freshwater and brackishwater conditions and culture cycles with mean cell dry weight of 706.98 ±285.52 and 479.79±204.53 mg L⁻¹, respectively. The highest chlorophyll a content was also observed in A. platensis cultivated in 4% ADPOME, in both freshwater and brackishwater conditions from both culture trials with mean chlorophyll a content at 10.12±6.10 and 8.40±5.23 mgL⁻¹ , respectively.